Critical success factors for a total quality culture: A structural model - Ana Cláudia Campos; Júlio da Costa Mendes; João Albino Silva; Patrícia Oom do Valle (Tourism & Management Studies)
Research on quality based on the cultural perspective claims that, more than an implementation of tools and techniques, quality is the outcome of cultural factors, namely organisational values and practices among which leadership and employee working patterns are of paramount importance. The development of a total quality culture is a strategic issue for the achievement of stakeholder satisfaction and business competitiveness in a highly demanding and uncertain business environment. In this research a model integrating the critical success factors for a total quality culture was tested in organisations of two subsectors of the tourism industry, using the SEM (Structural Equation Models with Latent Variables) approach by means of the PLS (Partial Least Squares) technique. Main findings corroborate that leadership and employee empowerment are key success factors for a total quality culture, thus reinforcing the principle that everyone in the organisation is responsible for quality. However, organisational information and communication practices were not found to be key success factors.